If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-5)+4x=9x+18
We move all terms to the left:
3(x-5)+4x-(9x+18)=0
We add all the numbers together, and all the variables
4x+3(x-5)-(9x+18)=0
We multiply parentheses
4x+3x-(9x+18)-15=0
We get rid of parentheses
4x+3x-9x-18-15=0
We add all the numbers together, and all the variables
-2x-33=0
We move all terms containing x to the left, all other terms to the right
-2x=33
x=33/-2
x=-16+1/2
| 1/4+z=1/3 | | 13m+3m=7m-36 | | 125=25^2x | | 63.30=63.3r | | 19^(6x)-5=14 | | P=3x-2 | | 5x/8-x/4=6 | | 6x+3x-5x=30 | | 2/3x-5/6=12 | | 2x2+3x-6=0 | | 59=-y+208 | | 10^-6=(10^x)/(10^2) | | x+6+12x=90-3x | | 227=-u+66 | | -1/2(x-12)=4 | | -x+4(-3x+18)=-19 | | t/−15=−3 | | 6(3x–7.2)=25.2 | | 33-5x=16+12x | | 73-u=181 | | 9(x+4)=9x+36 | | Y=100*0.5^x | | 0=2(X+6)-9x | | 2.3r-5.2=-8.2+1.3r | | x+5=5x+14 | | 2/5a=-20 | | 98=6d+62 | | –13+5(x–2)+3(2x+5)=4(2x–6)+1 | | .5m+5.00=1.00m | | (y-2)/4=3 | | 13=a+3 | | 0.5(a+3)=0.2(2a+9) |